Efficacy of Sofosbuvir, Daclatasvir and Ribavirin Combination Therapy in Treatment Naïve Hepatitis C Patients at Tertiary Care Hospital of South Punjab - Qasim Umar, Rizwan Hameed, Muhammad Asif Gul, Yasir Abbas Zaidi, Shehryar Kanju, Dure Shahwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hepatitis C has gradually become endemic in Pakistan, with infectivity rates one of the highest in the world. The emergence of direct acting antivirals (DAAs) has become a ray of sunshine in eradicating this menace from this region. The combination of sofosbuvir, daclatasvir and ribavirin (SOF/DACLA/RIBA) has had phenomenal success all over the world in eradicating this virus. Our study aims to see the effectiveness of this regime in this part of the world. Methods: After approval from the institutional review board (IRB), retrospective analysis of data of treatment naïve patients who have been treated with the above mentioned regimen was collected to assess the efficacy by calculating the sustained virological response (SVR) at 12 weeks after completion of therapy. Results: Data of 300 patients (172 females, 128 males) was collected. Mean age was 39.66 years. Majority (almost 90%) of patients were from District Multan Age range was from 18 years to 60 years. Eighty-three percent of the patients were non-cirrhotics, 15.7% had compensated cirrhosis, while only 1 % had decompensated cirrhosis. Out of the 300 patients, 291 patients had undetectable HCV RNA on polymerase chain reaction (PCR) at 12 weeks after completion of treatment, achieving SVR rates of 97%. There was no significant association of SVR rates with gender and age of patients. Conclusion: The combination of SOF/DACA/RIBA is highly efficacious for treatment of hepatitis C patients. Keywords: sofosbuvir, daclatasvir, efficacy, sustained virological response, hepatitis C